Growth media derived from solid waste for orchid Dendrobium kingianum culture - Ma, Nyuk Ling; Khoo, Shing Ching; Loke, Lim Kar; Lam, Su Shiung; Tan, Suat Hian (Penerbit Universiti Kebangsaan Malaysia, 2019)
Food waste and diaper waste contribute to top three ranking solid wastes in Malaysia. Many studies show that urine and food waste can be used as plant fertilizer but less attention has been given to the recycling of used diaper. Therefore, this study was conducted to formulate Dendrobium kingianum growing media by utilizing diaper waste and selected food waste: banana peels, coffee waste and eggshells. The chemical composition in diaper waste and food waste were determined by using ICP-OES method. Biochar derived from oil palm waste, sugarcane and sawdust were tested to reduce and neutralize the high ammonium content from diaper waste. Biochar derived from oil palm waste showed the best reduction of ammonium in diaper waste. Survival and growth performance of Dendrobium kingianum was observed and recorded. Results show that orchid in diaper formulated growth media T3 showed the best adaptation and growth performance with highest percentage of healthy leaves and number of absorption roots within 3 weeks observation period. These results revealed that diaper waste could be recycled as orchid growing media by formulating with food waste and biochar.